Indigenous food sovereignty is constrained by "time imperialism". Issue 133 (July 2022) - Ferguson, Caroline E.; Marie Green, Kristen; Switzer Swanson, Shannon
Graphical abstract: Highlights: Indigenous food sovereignty is subject to global and local stressors. Colonialism has reconfigured time in Indigenous communities. The wage economy and formal schooling require time demands that limit food harvesting. Natural cycles and human-induced environmental changes affect harvesting time. We propose a framework "time imperialism" to describe the restructuring of time. Abstract: Food sovereignty, which goes beyond food security to include culture, knowledge systems, labor practices, and ecosystem dynamics, is critical to Indigenous self-determination. Yet the reconstruction of time according to colonial values and the capitalist political economy constrains the ability of Indigenous peoples to exercise food sovereignty. In three case studies of coastal Indigenous harvesters from Alaska, USA; Palau; and Indonesia, we document how the social, cultural and political aspects of time restrict food sovereignty. Using interviews, participant observation and surveys, we found that: 1) food harvesting and the intergenerational sharing of Indigenous ecological knowledge was constrained by the time demands of the capitalist wage economy and formal schooling; 2) harvesting of wild foods was often already limited to narrow windows by natural constraints such as tides and weather systems; and 3) human-induced environmental changes further increased the time required for harvesting. We also found that Indigenous harvesters are meeting these challenges by reprioritizing and reimagining the harvest of Indigenous foods. These cases show that the dominant construction of time is intertwined with capitalism and tangibly limits the exercise of Indigenous food sovereignty. We propose a new framework to describe this phenomenon, which we call "time imperialism." We contend that this unrecognized form of imperialism imposes unique constraints to Indigenous self-determination and call for policies that explicitly address the impact of time on food sovereignty.